A Response to Jacques Derrida’s Plea - AZOUI, Samih (Journal of Human Sciences, 2025)
The definition of the mission of the University has always been a daunting challenge. For more than a century, the (British) University has been steadily straying from the creation and transmission of the light of knowledge to that of light knowledge. The present article has focused on this deviation and looked into its course to contend that it is the departure of the debate on defining the mission of the University from its original academic and liberal attributes to the recently assigned technical and vocational tasks which has actually compelled Jacques Derrida (2004) to make his groundbreaking call for the recovery of the enlightenment that the University has failed to follow. The participation of social philosophers of higher education is salutary and must bring the liberal purpose of the University (in the UK and worldwide) back to the core of the debate.